2018
DOI: 10.1051/0004-6361/201731326
|View full text |Cite
|
Sign up to set email alerts
|

Photometric redshift estimation via deep learning

Abstract: Context. The need to analyze the available large synoptic multi-band surveys drives the development of new data-analysis methods. Photometric redshift estimation is one field of application where such new methods improved the results, substantially. Up to now, the vast majority of applied redshift estimation methods have utilized photometric features. Aims. We aim to develop a method to derive probabilistic photometric redshift directly from multi-band imaging data, rendering pre-classification of objects and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(67 citation statements)
references
References 33 publications
0
63
0
Order By: Relevance
“…Finally, Deep Machine Learning (DML), the current state of the art in computer science, has been also applied to problem of photo-z estimation in [e.g. 51,52]. DML is based on normal neural networks, but with many thousands of neurons in each hidden layer.…”
Section: B Data Driven Methodsmentioning
confidence: 99%
“…Finally, Deep Machine Learning (DML), the current state of the art in computer science, has been also applied to problem of photo-z estimation in [e.g. 51,52]. DML is based on normal neural networks, but with many thousands of neurons in each hidden layer.…”
Section: B Data Driven Methodsmentioning
confidence: 99%
“…aanda 2018), classification of light curves (Charnock & Moss 2017;Pasquet-Itam & Pasquet 2017). Thanks to the speed boost from Graphic Processing Units (GPU) technology and large galaxy spectroscopic sample such as the SDSS survey, Hoyle (2016);D'Isanto & Polsterer (2018) showed that Deep Convolutional neural network (CNN) were able to provide accurate phototometric redshifts from multichannel images, instead of extracted features, taking advantage of all the information contained in the pixels, such as galaxy surface brightness and size, disk inclination, or the presence of color gradients and neighbors. To do so, Hoyle (2016) used a Deep CNN inspired by the architecture of Krizhevsky et al (2012a), on 60×60 RGBA images, encoding colors (i − z, r − i, g − r) in RGB layers and r band magnitudes in the alpha layer.…”
Section: Introductionmentioning
confidence: 99%
“…SDSS, Beck et al 2016) and optical QSOs (e.g. Ball et al 2007Ball et al , 2008D'Isanto & Polsterer 2018). For X-ray AGN, though, only SED fitting techniques had been used (Salvato et al 2009;Hsu et al 2014), up until recently.…”
Section: Introductionmentioning
confidence: 99%